Partially Systematic Line-plot Surveys - Rao, J. N. K. (Indian Forester, 1958)
Nair and Bhargava ( 1951 ) and Mokashi ( 1956) have investigated the possibility of random line-plot surveys, i.e., strips taken at random and plots within each selected strip taken at random, for the forests of Mount Stuart, Madras and Dangs Division, Bombay respectively. They found that random line-plot surveys give more precise estimates than strip surveys for a given intensity of sampling. In this paper, the possibility of partially systematic line-plot surveys, i.e., strips taken at random and within each selected strip plots taken systematically (i.e., at regular intervals with a random start) is investigated. Partially systematic line-plot surveys provide valid estimates of the standard error as in the case of random line-plot surveys. The same data of Mount Stuart forest used by Nair and Bhargava ( 1951 ) are taken, and for different intensities of sampling within a strip the number of strips required to get a percentage standard error of 5 are found out and are compared with that required for random line-plot surveys. It is found that partially systematic line-plot surveys require less intensity of sampling than random line-plot surveys and is therefore preferable to the latter. Partially systematic line-plot surveys will also be preferable to the commonly used totally systematic line-plot surveys, i.e., strip selected systematically and within each selected strip plots selected systematically, since the latter do not provide valid estimates of the standard error though they may be more precise than the former for the same intensity of sampling.